More award-winning science fair projects - Bochinski, Julianne Blair, 1966-; DiBiase, Judy (Hoboken, N.J. : J. Wiley, 2004)
Presents 35 award-winning science fair projects, a section on how to do a science fair project, updates to science fair rules and science supply resources, as well as new material on useful web sites.
Includes index.
Keywords: Science fairs -- Juvenile literature; Science projects -- Juvenile literature; Science -- Experiments -- Juvenile literature; Experiments; Science projects; Science -- Experiments